“Aquel romance bárbaro”: Gossip as Popular Imaginary in the Novel Una de dos, by Daniel Sada. - Blanco Ramos, Roberto Antonio (2020)
This article proposes to analyze the construction of the imaginary of gossip in the narrative language of Mexican writer Daniel Sada. The text seeks to answer the following questions: How can different forms of orality, in this case gossip, support literature within the narrative construction of language? And how could it be established as a popular imaginary within the symbolic representation of narrative language? To carry out this analysis, the research addresses discursively the novel Una de dos, published in the year 1994. The work is divided into several sections that encompass the central problem. In the first section, the literary tradition of Northern Mexico is examined, in order to contextualize and classify the work of Daniel Sada. In the second section, the main characteristics of its narrative language are analyzed. Thus, in the third, the imaginary of the gossip present in the novel is examined and exemplified.